Mediasi Penerapan Community Based Tourism pada Pengaruh Kunjungan Wisata Terhadap Pendapatan Masyarakat di Objek Wisata Pantai Kabila Bone - Usman, Usman; Mattoasi, Mattoasi; Taruh, Victorson (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
Gorontalo is known as one of the provinces rich in natural beauty, especially in the marine tourism sector. The philosophy of life of its people who combine custom with sharia and uphold the values of local wisdom makes it even more attractive to tourists. The purpose of this study is to evaluate the impact of tourist visits and the application of the Community Based Tourism model on the level of community income. The research method used is quantitative, with data collection through questionnaires. The sampling technique used purposive sampling and as many as 86 respondents. Statistical data analysis used in this study is non-parametric with Partial Least Squares - Structural Equation Model (PLS-SEM) with SmartPLS Version 04 software application. The results of this study indicate that tourist visits have a positive and significant effect on community income at Bone Bolango beach tourism objects, tourist visits have a positive and significant effect on the application of the community-based tourism model at Bone Bolango beach tourism objects, the application of the community-based tourism model has a positive and significant effect on community income at tourist objects and tourist visits have a positive and significant effect on community income through the application of the Community Based Tourism model at Bone Bolango beach tourism objects.